Customer Satisfaction Index of Singapore 2017: Full Year Overview - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2018)
The Customer Satisfaction Index of Singapore (CSISG) computes customer satisfaction scores at the national, sector, sub-sector, and company levels. The CSISG serves as a quantitative benchmark of the quality of goods and services produced by the Singapore economy over time and across countries. The fourth quarter results mark the end of measurement for CSISG 2017. Singapore’s 2017 national score was computed using the data collected during these four quarters.